Aquatic telemetry advances and applications - Spedicato, Maria Teresa; Lembo, Giuseppe; Marmulla, Gerd (Rome, Italy Coispa Tecnologia & Ricerca and Fod and Agriculture Organization of the United Nations, 2005)
Proceedings of the Fifth Conference on Fish Telemetry held in Europe Ustica, Italy, 9-13 June 2003
Keywords: Fishes -- Behavior -- Research -- Congresses; Animal radio tracking -- Congresses